GENDER AND VULNERABILITIES IN ADOLESCENCE: COMPARATIVE ANALYSIS OF HEALTH AND EDUCATION INDICATORS AMONG STUDENTS IN FORTALEZA (2009–2019) (International Seven Journal of Multidisciplinary, 2025)
This study conducted a comparative analysis, by sex, of the temporal evolution of indicators across the thematic areas of violent behavior, exposure to violence, mental health, access to services, and the school environment among adolescents in Fortaleza, from 2009 to 2019, based on data from the National School Health Survey (PeNSE). A quantitative approach was used, with proportion analysis and linear trend tests (p